CO2 Storage Screening Criteria Based on Seal Capacity in Indonesia - Destiana, Syifa; Dedy Irawan; Prasandi Abdul Aziz; Ika Merdekawati (Scientific Contributions Oil and Gas, 2025)
CO2 storage screening ensuring the long-term containment of injected CO2 and the integrity of carbon capture and storage. In Indonesia, robust seal evaluation is constrained by the limited availability of caprock core data. This study develops a dimensionless Caprock Quality Index (CQI) as a practical CO2 storage screening tool based on displacement pressure (Pd) and caprock thickness (h). Displacement pressure is estimated using an empirical Pd equation derived from existing caprock core data. The CQI provides a quantitative classification of seal quality within the 0-1 range, where values closer to 1 indicate better caprock quality. Based on the data availability of this study, the results show that the Banggai and Salawati basins currently exhibit the highest CQI, indicating strong suitability for CO₂ storage. This study provides a framework for conducting preliminary CO₂ storage screening, particularly valuable in settings where caprock core data are sparse and contributes to the development of a more efficient, data-driven framework for future CCS planning and implementation.